The Relation Between Self-Esteem Development and Learning Breaststroke Swimming Performance - Khitam Mousa Ay (European Scientific Journal, ESJ, 2016)
This study investigates the relation between self-esteem development and learning to perform the breaststroke swimming skill. Twenty four female students from physical education faculty at the university of Jordan (19 ± 0.5) years of age, who were assigned in swimming course (2) in the first semester 2014/2015. After completing the self-esteem Questionnaire (Robson Self-Esteem Questionnaire, 1989) the subjects were randomly divided into two groups: experimental group (n=12) received physical practice of the breaststroke swimming skill performance, and dialogues for self-esteem development, and control group (n=12) received only physical practice of the breaststroke swimming skill performance. Two measurements were taken; both groups were measured at the beginning (pre-test), in order to establish that all students started at the same level of performance and global self-esteem level, after the pre-test of the breaststroke skills performance, all subjects filled out the self-esteem questionnaire. After the completion of the intervention the final measurements were taken (post-test), to note the impact of the intervention on the student`s performance in breaststroke swimming skills and selfesteem improvement. Statistical analysis included t-Test for mean at pre and post test for the two groups and t-Test for mean at post test in the two groups. The results showed significant differences (p < 0.05) in post test between the two groups in favor of the experimental group. In conclusions learning new swimming skills performance engaged to dialogues for self-esteem development enhanced learning and improved skills performance of the breaststroke swimming.